Answer:
The cost of one hot dog is $1 and the cost of one hamburger is $1.75
Explanation:
We are going to make 2 equations with which the problem tells us
h = hamburger cost
d = hot dog cost
3d + 2h = $6.50
3h + 2d = $7.25
we clear the h in the first equation
3d + 2h = $6.50
2h = 6.50 - 3d
h = (6.50 - 3d)/2
h = (6.50 - 3d)/2
h = (3.25 - 3/2 d)
we replace the value of h in the second equation by (3.25 - 3/2 d)
3h + 2d = $7.25
3(3.25 - 3/2 d) + 2d = $7.25
9.75 - 9/2 d + 2d = 7.25
- 9/2 d + 2d = 7.25 - 9.75
-5/2 d = - 2.5
d = -2.5 / (-5/2)
d = 1
we replace the value obtained from d in the first equation
h = (3.25 - 3/2 d)
h = (3.25 - 3/2 *(1))
h = 3.25 - 1.5
h = 1.75
The cost of one hot dog is $1 and the cost of one hamburger is $1.75